Welfare Practices In Calf Rearing: A Comparative Study In Madhubani District Of Bihar - Kumar, Vijay; Singh , B.P.; Kumar , Rajesh (Indian Journal of Veterinary Sciences and Biotechnology, 2011)
Welfare management of calf were framed to be of mixed aspect i.e. some practices were satisfactory and some were below the standards. Colostrum feeding was practiced to calf after release of placenta which might take longer time while recommendation is to provide colostrum within one hour of birth. Generally, there was no practice of applying disinfectant on naval cord. Further, castration was done by desi (local) method by majority of farmers which was very painful and unhygienic. The major constraints encountered by farmers to follow proper welfare practices were lack of money, lack of knowledge and veterinary doctors in vicinity. Perception of veterinary officers regarding above practices were poor to satisfactory.
Keywords: Calf Rearing; Constraints; Management; Welfare